The African continent should consider a harmonized consultative and collaborative effort towards coordinated policy and regulatory guidelines across the fields of biotechnology - Masehela, Tlou Samuel; Barros, Eugenia (Frontiers in Bioengineering and Biotechnology, 2023)
The advances in the field of biotechnology (and bioengineering) over the past decades has allowed the precise development of new products across the agricultural, environmental, and pharmaceutical sectors. This has led to the need to evaluate the relevance and applicability of existing policies and frameworks that regulate the current transgenic technologies. On the African continent, there are delays in the development and implementation of biosafety policies and regulations. Most African countries formulate their policies, regulations, and frameworks by following The Convention on Biological Diversity’s (CBD) guidelines. Although the CBD documents are continually evolving, this happens at a slower pace. It is becoming increasingly important for countries to deal swiftly with the advances in biotechnology in a manner that balances the regulatory complexities, while safeguarding the net gains for human health, the environment, and the economy. For the African countries, some of these net gains are similar, while concerns and perceived risks associated with the adoption and use of the technology are also common. Furthermore, the challenges relating to capacity, knowledge, and skills to address some of the regulatory complexities. In this article we explore the advancement of some African countries in the development and implementation of various biosafety policies and details the challenges and constraints faced by those countries that are lagging behind. We conclude by outlining identified opportunities for neighbouring and regional countries to assist one another and work in a more organised and coordinated approach towards developing, implementing, and strengthening their respective biosafety policies, regulations, and frameworks.